Psychedelics and workplace harm - Viña, Sean Matthew; Stephens, Amanda Layne (Frontiers in Psychiatry, 2023)
This study aims to understand the relationship between Lifetime Classic Psychedelic Use (LCPU), employment status, and weekly work hours on levels of psychological distress. The data used for this analysis is pooled from the National Survey of Drug Use and Health (NSDUH) from 2008-2019 and includes a sample size of 484,732 individuals. The findings suggest that LCPU and being employed are independently associated with better health. Additionally, the results indicate that psychedelic use is associated with lower distress for those who are employed, volunteer, retired, or permanently disabled. However, those who are unemployed, full-time students, or homemakers may experience higher levels of distress with psychedelic use. Interestingly, the analysis also suggests that those who use psychedelics are working longer hours per week before experiencing an increase in stress. Overall, the study suggests that psychedelics are not likely to have a negative impact on employment outcomes.